Raman spectroscopy investigations of chemically derived zigzag edge graphene nanoribbons - R. Nishinakagawa; K. Matsuda; T. Arai; A. Sawada; T. Terashima (AIP Advances, 2013)
We fabricated graphene nanoribbons (GNRs) chemically derived from expandable graphite. All GNRs exhibit atomically smooth edges that extended over their entire length. We investigated four of the fabricated GNRs using Raman spectroscopy. Two of the investigated GNRs show Raman spectra with a missing D-band peak, while D-band peaks can be clearly observed for the other two GNRs. The two GNRs which do not show the D-band peak are GNRs with zigzag edges, and the two other GNRs which show clearly the D-band peaks are possibly GNRs with armchair edges.